2012
DOI: 10.1016/j.brainres.2012.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Conflict monitoring and resolution: Are two languages better than one? Evidence from reaction time and event-related brain potentials

Abstract: An advantage for bilingual relative to monolingual young adults has been found for cognitive control tasks, although this finding is not consistent in the literature. The present investigation further examined this advantage using three tasks previously found to be sensitive to the effect. Furthermore, both behavioral and event-related brain potential (ERP) measures were included. Monolingual (n=25) and highly proficient bilingual (n=26) young adults completed a Stroop, Simon, and Eriksen flanker task while el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
168
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(198 citation statements)
references
References 60 publications
20
168
4
Order By: Relevance
“…Consistently, bilingual executive processing advantages have not been observed in studies with large sample sizes (e.g., Duñabeitia et al, 2014;Gathercole et al, 2014). Using similar tasks, other researchers have also failed to observe inhibitory control advantages in bilingual adults (Kousaie & Phillips, 2012a, 2012b). …”
Section: Bilingual Working Memorymentioning
confidence: 96%
See 3 more Smart Citations
“…Consistently, bilingual executive processing advantages have not been observed in studies with large sample sizes (e.g., Duñabeitia et al, 2014;Gathercole et al, 2014). Using similar tasks, other researchers have also failed to observe inhibitory control advantages in bilingual adults (Kousaie & Phillips, 2012a, 2012b). …”
Section: Bilingual Working Memorymentioning
confidence: 96%
“…More recent studies have failed to observe evidence of a bilingual advantage in inhibitory control or other executive abilities (e.g., Duñabeitia et al, 2014;Gathercole et al, 2014;Goldman, Negen & Sarnecka, 2014;Hernández, Martin, Barceló, & Costa 2013;Kousaie & Phillips, 2012a;Kousaie & Phillips, 2012b;Namazi & Thordardottir, 2010;Paap & Greenberg, 2013;Paap & Liu, 2014). Duñabeitia et al (2014) Goldman et al (2014) found that bilingual and monolingual children performed equivalently on a task that required them to attend to the number of stimuli while ignoring their size.…”
Section: Bilingual Working Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…We focus on response latencies for reasons of comparability Second, for studies that did not trim the data, there was a big variation in terms of the maximum time allowed for making a response. For example, in Kousaie and Phillips (2012) 750 ms were allowed for making a response, meaning that in this particular design it was not possible to observe responses slower than 750 ms. This is equivalent to trimming the data at 750 ms. For these reasons, we focused on maximum response times being included in analyses (Fig.…”
Section: Meta-analysismentioning
confidence: 99%